Generation of ultra-sound during tape peeling - Marston, Jeremy O. (Nature Publishing Group, 2014)
We investigate the generation of the screeching sound commonly heard during tape peeling using synchronised high-speed video and audio acquisition. We determine the peak frequencies in the audio spectrum and, in addition to a peak frequency at the upper end of the audible range (around 20 kHz), we find an unexpected strong sound with a high-frequency far above the audible range, typically around 50 kHz. Using the corresponding video data, the origins of the key frequencies are confirmed as being due to the substructure “fracture” bands, which we herein observe in both high-speed continuous peeling motions and in the slip phases for stick-slip peeling motions.